2016
DOI: 10.1080/09720502.2015.1047591
|View full text |Cite
|
Sign up to set email alerts
|

Extended convolution model to bayesian spatio-temporal for diagnosing the DHF endemic locations

Abstract: We develop a Bayesian spatio-temporal model based on a spatial Poisson-Lognormal convolution model. The convolution model consists of two component, i.e.; heterogeneity (fixed effects) and uncertainty (local and global random effects). We introduce an additional component in the development model so-called temporal trend. The developed model is adjusted based on dengue hemorrhagic fever (DHF) characteristics data. The DHF cases are considered as two-level hierarchical data since the cases are measured at small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…is paper introduces vector matrix and multidimensional convolution ( ⊗ ) to extend PCNN, which is called the multidimensional PCNN model for short, and the application of PCNN is extended so that PCNN can directly realize multidimensional image's edge location [20][21][22][23].…”
Section: Pcnn Edge Location Of Multidimensional Imagementioning
confidence: 99%
“…is paper introduces vector matrix and multidimensional convolution ( ⊗ ) to extend PCNN, which is called the multidimensional PCNN model for short, and the application of PCNN is extended so that PCNN can directly realize multidimensional image's edge location [20][21][22][23].…”
Section: Pcnn Edge Location Of Multidimensional Imagementioning
confidence: 99%
“…ST-CAR models have been used to study the effect of air pollution on human health, 24 substance abuse, and its relationship with child abuse, 25 influenza, 26 and DENF. [27][28][29] More research is necessary to examine the local variations in DENF transmission dynamics at very fine spatial and temporal scales. Delmelle et al 30 used a geographically weighted regression (GWR 31 ) model which identified six significant socioeconomic and environmental independent variables (including proximity to tire shops and population density) of DENF rates in Cali, Colombia, at the neighborhood level.…”
Section: Introductionmentioning
confidence: 99%
“…ST-CAR models have been used to study the effect of air pollution on human health, 24 substance abuse, and its relationship with child abuse, 25 influenza, 26 and DENF. 27 29 …”
Section: Introductionmentioning
confidence: 99%
“…The DHF dynamics have also gained prominence recently since climate change or global warming is predicted to have unexpected effects on its incidence [ 4 , 5 ]. The complexities in the life cycle of the mosquito, highly complex environmental and social interactions, unforeseen consequences of climate change, and population migration between endemic and non-endemic areas continued to contribute to the massive burden of morbidity and mortality accompanying the DHF [ 6 , 7 ]. With no effective vaccine, eradicating mosquito larvae as early as possible is the only advisory prevention.…”
Section: Introductionmentioning
confidence: 99%